Becoming Ayi: Chinese female domestic workers' transformation from docile bodies to wilful subjects. - Chen, Zhen Troy; Kuang, Xianwen; Liu, Xi (Journal of Gender Studies, 2026)
The term 'Ayi' (Auntie) has often been used in a less discriminatory way than 'Baomu' (Nanny, Maid) to describe female domestic workers from outside the immediate family. Research into the development of the concept of ayi interrogates the identity construction and transformation of female domestic workers as part of the emergence of a post-socialist market economy. To understand the lived experiences of this social group which could provide us with insights into gender equality issues in China, we have collected and analysed data from in-depth interviews and focus group with female domestic workers from rural backgrounds. Existing research suggests that ayi has become a split-subject, anchoring a historical moment within the fast urbanization process in a patriarchal and neoliberal post-socialist China featured by intertwined social inequalities. The idea of 'becoming ayi' provides a new conceptualization and contextualization of identity negotiations and cultural production intersecting region, the rural–urban divide, class, and gender where female subjects have usually been viewed as either passive or active. The conceptualization of 'becoming ayi' works as a necessary intervention that replaces the previous binary oppositions between subject and other, agency and victimization, central and peripheral to better understand the identification of female domestic workers in contemporary China.